2020
DOI: 10.5664/jcsm.8180
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Lung Disease and Obstructive Sleep Apnea (OLDOSA) cohort study: 10-year assessment

Abstract: Study Objectives: Asthma, chronic obstructive pulmonary disease (COPD), and obstructive sleep apnea (OSA) are very prevalent disorders. Their coexistence in the same individual has an unclear effect on natural history and long-term outcomes. Methods: The OLDOSA (Obstructive Lung Disease and Obstructive Sleep Apnea) cohort enrolled 4,980 veterans with an acute hospitalization and in whom asthma, COPD, OSA, overlapping conditions, or none of these disorders at baseline had been diagnosed. Pulmonary function, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…I was glad to read a positive study regarding the effects of continuous positive airway pressure therapy on patients with obstructive lung disease and obstructive sleep apnea (OSA). 1 However, the 10-year all-cause, cumulative mortality rate in the obstructive lung disease and obstructive sleep apnea cohort was 52.8%, which is much higher than the study by Marin et al 2 of similar patients with overlap syndrome and a mortality rate of 32.7%, with a median follow-up of 9.4 years. This is all the more concerning because the baseline forced expiratory volume in 1 second (FEV1) in their study was 75.4% (chronic obstructive pulmonary disease+OSA).…”
mentioning
confidence: 56%
“…I was glad to read a positive study regarding the effects of continuous positive airway pressure therapy on patients with obstructive lung disease and obstructive sleep apnea (OSA). 1 However, the 10-year all-cause, cumulative mortality rate in the obstructive lung disease and obstructive sleep apnea cohort was 52.8%, which is much higher than the study by Marin et al 2 of similar patients with overlap syndrome and a mortality rate of 32.7%, with a median follow-up of 9.4 years. This is all the more concerning because the baseline forced expiratory volume in 1 second (FEV1) in their study was 75.4% (chronic obstructive pulmonary disease+OSA).…”
mentioning
confidence: 56%
“…As pointed out before, 2 when one compares the OLDOSA with the study by Marin et al 3 on individuals with COPD and COPD-OSA overlap syndrome, our patients had a much higher mortality rate (52.8% vs 32.7%), at least in part because of their older age (61 ± 13 years in OLDOSA vs 57 ± 8 years) and their being much "sicker" (mean CCI was 5.3 ± 3 vs 1.2 ± 1 in the Spanish study), despite better average lung function in OLDOSA participants. 2 Whereas CCI categorizes the presence of comorbidities as nominal or ordinal variables, and data are typically extracted from various administrative databases, in our study, we "curated" all diagnoses by individual chart review and strict adjudication criteria. The author 1 suggests that we use propensity score analysis for mortality (which could explain, for example, worse vital outcomes in those with solid tumors, myocardial infarction, congestive heart failure, COPD, chronic kidney disease, or peripheral vascular disease).…”
mentioning
confidence: 57%
“…The median time to death was 2.7 years, perhaps consistent with the fact that recent hospitalizations (of any cause) may herald worse short-term outcomes. 2 Mortality was higher in older participants, in men, in white patients, in those with coexisting conditions (as assessed by the Charlson Comorbidity Index [CCI]), and in patients with a lower forced expiratory volume in 1 second (FEV 1 ). We showed that in OSA, treatment initiation and superior adherence to positive airway pressure (PAP) therapy were associated with lower mortality, independently of sex, race, age, comorbidities, weight, or lung function.…”
mentioning
confidence: 99%
“…This result is counterintuitive and not previously described. Although association between COPD and OSA 46 , 47 is reported, it is to be expected that chronic lung disease is related to greater severity of OSA. The design of this study does not allow us to explore the causes of this inverse association between OSA severity and COPD prevalence.…”
Section: Discussionmentioning
confidence: 98%